Nonlinear and Non-Gaussian State-Space Modeling with Monte-Carlo Simulations - Mariano, Roberto S. (Institutional Knowledge at Singapore Management University, 1998)
We propose two nonlinear and nonnormal filters based on Monte Carlo simulation techniques. In terms of programming and computational requirements both filters are more tractable than other nonlinear filters that use numerical integration, Monte Carlo integration with importance sampling or Gibbs sampling. The proposed filters are extended to prediction and smoothing algorithms. Monte Carlo experiments are carried out to assess the statistical merits of the proposed filters.